Characterization of Attributes in Dehusked Coconut - Monicka, A. Asha; Pandiarajan, T.; Ganapathy, S.; Rani, C. Indu; Sathy, R. (Journal of Agricultural Engineering, 2018)
Selected physical properties of dehusked coconut as length, width, thickness, geometric mean diameter, sphericity, surface area, bulk density and true density were investigated. Compositional changes in coconut fruits, including volume and weight, shell weight, weight of mature coconut water, wet and dry flesh weight, thickness of the flesh and shell were also evaluated. The average fruit length, major diameter and minor diameter were 99.2±13.3 mm, 91.5±8.9 mm, and 89.5±8.7 mm, respectively; while the sphericity, true density, bulk density and surface area were 0.90±0.05, 998±68.8 kg.m-3, 483±37.3 kg.m-3 and 274.2±50.4 cm2, respectively. The frequency distribution of the major diameter and the fruit mass followed the Gaussian model. Correlations between fruit characteristics were also determined. Results indicated that fruit weight and total wet flesh weight were closely correlated, and both of these characteristics can be used as an indicator of fruit size.